Fire risk in a control room of a municipal solid waste plant - Ferreira, Emanuel (2012)
This paper presents the results of the quantitative probabilistic assessment of the fire risk of the control room core of a treatment plant of urban solid residues. To quantify the fire risk it is used the Building Fire Safety Evaluation Method (BFSEM). The application of BFSEM to the compartment allowed the determination of the probabilities of occurrence of the different ways of fire extinction and the probability of flashover.